The Cdc42/Par6/aPKC Polarity Complex Regulates Apoptosis-Induced Compensatory Proliferation in Epithelia. - Warner, S.J.; Yashiro, H.; Longmore, G.D. (Current Biology, 2010)
In response to stress- or tissue-damage-induced apoptosis, unaffected epithelial cells undergo compensatory proliferation to maintain the integrity of the epithelium. Proximal signals regulating this response are not fully understood, but c-Jun N-terminal kinase (JNK) activity appears to be critical for both apoptosis and compensatory proliferation. Disruption of epithelial cell apical-basal polarity occurs in early cancer development and is often correlated with increased proliferation by means not fully characterized. We considered whether disruption of the various polarity complexes could provide signals identifying damaged epithelial cells and thus lead to apoptosis-induced compensatory proliferation.We identify the Cdc42/Par6/atypical protein kinase C (aPKC) Par polarity complex as uniquely and specifically regulating apoptosis-induced compensatory proliferation in Drosophila epithelia. Genetic depletion of individual components or disruption of formation and localization of this complex, but not other polarity complexes, induces JNK-dependent apoptosis and JNK-dependent compensatory proliferation following radiation injury. When apoptosis execution is blocked, by p35 expression, Cdc42/Par6/aPKC-depleted tissues uniquely hyperproliferate, leading to tissue and organ overgrowth. Disruption of Cdc42/Par6/aPKC leads to activation of JNK through increased Rho1 and Rok activity and Rok's capacity to activate myosin but not F-actin.We show that the Cdc42/Par6/aPKC polarity complex influences both a physiologic compensatory proliferation response after irradiation injury and a contrived compensatory non-cell-autonomous hyperproliferation response when cell-autonomous apoptosis, resulting from Cdc42/Par6/aPKC disruption, is inhibited. These results suggest the possibility that in cancer where apoptotic regulation is disrupted, loss of Cdc42/Par6/aPKC polarity complex organization or localization could contribute to tumor hyperproliferation and explain how polarity disruption contributes to tumor development.